Air pollution and its impact on the concentration of airborne fungi in the megacity of São Paulo, Brazil - Castro e Silva, Dulcilena de Matos (Heliyon, 2020)
In the context of megacities in an urban environment, air quality is an important issue, due to the direct correlation to population's health. The biomonitoring of pollutants can indicate subtle environmental alterations, for that, anemophilous fungi can be monitored for changes in atmospheric conditions related to pollution. In the present study, the concentration of fungi and bacteria in the atmosphere was measured during a specific vehicle fleet reduction in the city of São Paulo, Brazil, from May 24 to 30, 2018, using impactor air samplers. The number of isolated developed colonies was related to atmospheric conditions and the concentration of other air pollutants constantly monitored. Aspergillus, Curvularia, Penicillium, Neurospora, Rhizopus and Trichoderma were identified. The number of colony-forming units increased by approximately 80% during the sampling period in response to environmental changes favored by the fleet reduction. This result implies the relation between fuel emissions, concentration of atmospheric pollutants, and the presence of viable fungal spores in the urban environment, which highlights the importance of combined public policies for air quality in large cities.